Social capital and local development in Swedish rural districts - Hans Westlund; Anette Forsberg; Chatrine Höckertin (European Regional Science Association (ERSA), 2002)
This paper studies local social capital in two Swedish rural districts. It concentrates on the relations between local political/public bodies and local development groups. The political bodies have acted somewhat differently towards local development initiatives in the two districts. This has resulted in differences in the number of development groups and in the social capital of local culture, leisure and service environments. There are, however, few examples of social capital in these environments spreading to changes in production environments, in the form of e.g. attitudes to entrepreneurship, risktaking, etc. The study supports the view that private and public actors can change local social capital. Local organizations who act as intermediate nodes between the local groups and the political bodies seem to be of special importance. However, our results suggest that changing local social capital is a long-term mission that demands sustainable work.
Keywords: 330